Analysis of Employee Readiness to Strengthen the Success of Digital Transformation in Public Institutions - Widya Ayu Ratnasari; Hermawan, Ancella Anitawati (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to analyze employee readiness in supporting the successful implementation of digital transformation at the Directorate General of Taxes (DGT). Using a qualitative approach, this research utilizes questionnaires and Focus Group Discussions so as to gain a more detailed perspective. The findings show that although employees show a high level of awareness and motivation, there are still gaps in understanding the implications of the transformation on daily tasks, especially for those with less experience. The complexity of the new system and existing communication challenges highlighted areas for improvement in training and reinforcement strategies. The research concludes that addressing these readiness gaps through targeted interventions, such as enhanced training and clear communication, is critical to sustaining employee engagement and achieving the desired transformation outcomes. This research provides actionable insights for public institutions that are undertaking digital transformation efforts.